Impact of Basketball Fan Behaviour on the Organization’s Brand (Baltic Journal of Sport and Health Sciences, 2017)
Background. In recent years sports industry has been growing fast, changing trends forced organizations to be creative and look for different ways to increase the competitiveness. Sport has become a business that meets all key management principles (Paul, 2003). In order for an organization to be profitable it is important to have good governance and effective marketing to attract new customers (Fillis & Mackay, 2014), in sports – fans that create added value for the clubs (Zagnoli & Radicchi, 2010). Some authors argue that fans are not only consumers, but also co-creators of the final product (Richelieu & Pons, 2011). The objective of this work was to measure the impact of basketball fan behaviour on the brand of sport organization. Methods. To measure the impact of basketball fan behaviour on the brand of sports organization methodological triangulation  was  used  in  the  study. The  research  consisted  of  3  stages:  questionnaire  (Sandanski,  Slavchev,  & Draganov, 2016), semi-structured interviewing I and semi-structured interviewing II. The study was partly conducted during the Erasmus+ Sport project “Fans Against Violence”. In Lithuania the aforementioned project was conducted by the Lithuanian Basketball Federation in the partnership with association “Aktyvistai”. 240 basketball fans from 5 different Lithuanian basketball clubs participated in the survey, 4 representatives from different basketball clubs and 4 fan leaders from different sport clubs were interviewed.Results and conclusions. The majority of basketball fans that participated in the survey were men aged 20–24 years (25.8%) and attended basketball matches by the guidance of hedonistic will (13.5%). The same men became basketball fans encouraged by other fans (25%). The strife between fans from different basketball teams goes from generation to generation and the main reason of aggressive behaviour is provocative actions from opposite fans (15%) and alcohol consumption (11.4%). While alcohol consumption is considered to be one of the main reasons to encourage fans’ aggression, only a small percentage of the respondents were strongly against the use of alcohol (7%). Summarizing all the results that were received during a semi-structured interviewing II it can be stated that the behaviour of the fans not only affects the brand of a basketball club, but is the main factor that impacts the brand of the club.Keywords:  brand, fans, aggression, basketball clubs.